CONSTRUCTION MODEL OF TOURIST VILLAGE DEVELOPMENT TOWARDS SMART ECO-TOURISM VILLAGE DESTINATION IN PAKSEBALI TO BECOME TOURISM ICON IN KLUNGKUNG REGENCY, BALI - I Wayan Pantiyasa; Ni Made Ayu Sulasmini; Putu Devi Rosalina (Institut Pariwisata dan Bisnis Internasional, 2019)
Paksebali is a newly developed tourist village in Bali. The development encounters challenges on the destination management, promotion, and stakeholders’ support. This study aimed at formulating strategy and construct the tourist village development model. Observation, interview, documentation, and FGD were used to collect data which then analyzed descriptively using qualitative and SWOT analysis. The study displayed the current condition of Paksebali is in the growth-oriented strategy. The construction of Paksebali development model towards smart eco-tourism village destination was initiated with identification of supporting components. This can be formulated into a tourist village development strategy including ICT-based management.Paksebali is a newly developed tourist village in Bali. The development encounters challenges on the destination management, promotion, and stakeholders’ support. This study aimed at formulating strategy and construct the tourist village development model. Observation, interview, documentation, and FGD were used to collect data which then analyzed descriptively using qualitative and SWOT analysis. The study displayed current condition of Paksebali is in the growth oriented strategy. The construction of Paksebali development model towards smart eco-tourism village destination was initiated with identification of supporting components. This can be formulated into tourist village development strategy including ICT-based management.